Characterisation of Pseudorabies Virus and Its Mutants - Allaudin, Zeenathul Nazariah (1999)

(untitled)
A plaque-purified pseudorabies virus (PrV-mAIP) was established from a field isolate. Following exposure to bromodeoxyuridine (BUdR) and iododeoxyuridine (IUdR), six drug resistant mutants namely PrV-BUdRI, PrVBUdR7, PrV-BUdRlO, PrV-IUdR5, PrV-IUdR9 and PrV-I UdRlO were derived from PrV-mAIP. These viruses were passaged for 47 times in chicken embryo fibroblast (CEF) monolayer. These viruses and also including PrV-mAIP and a reference PrY (PrV-CD) were characterised. Differences in their eclipse phase and virus titres were determined based on the virus growth. Prolonged eclipse period (increment of 14 hrs) and reduction of the peak titres were observed in PrV-BUdR7, PrV-I UdR9 and PrV-I UdRIO. DNA fingerprinting of the virus conducted with five restriction enzymes (RE) namely BamHI, Kpnl, HindIII, Sad and Bg/ll revealed variations in the number, size and migration rate of the restriction fragments only for BUdR resistant mutants. Generally, the RE pattern of all the IUdR resistant mutants appeared similar to PrY-mAIP, perhaps PrY is more stable to IUdR exposure. PrV-mAIP and PrY-CD were different, probably due to strain diversity of different geographical area. The absence of BamHI fragment 7 in both PrV-B UdRl and PrV-B UdR7 indicated highly to the loss of glycoprotein gE which is related to virulence. BamHI and KpnI enzymes appeared to be useful in discriminating the viruses. Alteration in the rate and type of cytopathic effect (CPE) were noticed in the viruses. The pronounced syncytium forming CPE in PrV-B UdR1, PrV-B UdR7 and PrV-IUdR10 indicated the loss of glycoprotein gC which usually plays a role in virus adsorption and cell to cell fusion. Similar to PrV-mAIP, the mutants were not pathogenic to mice. However, immunisation with these viruses conferred 100% protection (except PrV-B UdRlO) in mice upon challenge infection with the virulent PrY (PrV-CD). Mice immunised with PrV-B UdRlO produced similar antibody levels to those of PrV-mAIP but the degree of protection was reduced by 10%. The non pathogenic nature of the PrVs is known to be related to the deletion or mutation of the thymidine kinase (TK) gene. Thus, the 5' end of the gene of the PrVs was sequenced to identify any mutation. No variation was identified in the 399 bp nucleotide sequence data. However, the sequence showed various percentage of homology when pair-wise homology search were conducted against ten herpesviruses. Homology percentage ranged from 44.4% with herpesvirus of turkey (HVT) to the highly homologous (93.5%) of an established PrY strain NIA-3. These study demonstrate the variation among the mutants. All the mutants (except for PrV-B UdRlO) could be exploited for future research work for vaccine development. Genetic manipulation on these viruses such as insertion, deletion or recombination of foreign genes would be a valuable pathway to venture into.